The The Effect of Geothermal Waste as Filler Substitution on Stone Matrix Asphalt (SMA) Characteristics - Tolab, Laziqoh Zahatul; Fauziah, Miftahul (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
The Stone Matrix Asphalt (SMA) concrete mixture generally consists of aggregates, fillers, and additives. Stone dust filler has become a scarce component in the composition of the mix. One alternative filler that can be used is geothermal waste, which contributes to environmental pollution reduction and enhances its utility. This research investigates the influence of geothermal waste content as a substitute filler on the characteristics of Stone Matrix Asphalt (SMA) mixtures. The laboratory research follows the SNI 8129:2015, examining aggregate, filler, and asphalt materials. Subsequently, test specimens are fabricated to determine the optimum asphalt content (OAC). The OAC produces test specimens for Marshall, VCA, IRS, ITS, TSR, CL, and AFD tests. These tests are conducted at each geothermal waste filler substitution level, ranging from 0%, 10%, 20%, 30%, to 40%. The analysis results indicate that using geothermal waste as a filler in SMA mixtures performs optimally at a 40% substitution level. Increasing the substitution level enhances VFWA and density while decreasing VITM and VMA, as well as flow values. The SMA mixture achieves good stone-on-stone contact, demonstrated by the VCA value. As IRS and TSR indicate, geothermal waste improves stability and indirect tensile strength, enhancing the mixture's durability. Geothermal waste enhances the overall integration and homogeneity of the mix, making it resistant to plastic deformation and high temperatures, as observed in CL results.